Drug-like properties of anticancer molecules elucidated from Eichhornia crassipes - Mtewa, Andrew G; Deyno, Serawit; Ngwira, Kennedy; Lampiao, Fanuel; Peter, Emanuel L; Ahovegbe, Lucrece Y; Ogwang, Patrick E; Sesaazi, Duncan C (Journal of Pharmacognosy and Phytochemistry, 2018)
Eichhornia crassipes is reported to have molecules that are active against liver, cervical, breast cancers and melanoma cells. This systematic review was conducted according to Cochrane hand book of systematic review and guidelines for systematic reviews aiming to explore the potential that the plant has in providing drug leads against cancer. The results show that only a few molecules (10) have been elucidated from leaves of the plant and shown to be active against cancers. The molecules are alkaloids and tepernoids. Some drug-like properties (Solubility, permeability, lipophilicity and melting point) of a few of the compounds are known. Drug-like properties of the compounds elucidated from the roots, flowers and stem of Eichhornia crassipes, as well as other compounds from the leaves are yet to be determined. It is important to further explore these molecules as well as more from this promising plant for the developing of better anticancer drugs
Keywords: Lipophilicity; Permeability; Drug-leads; Hit molecules; Drug designing; Drug development